The Valkyrie Protocol - Weber, David 1952-; Holo, Jacob (Riverdale, NY : Baen, 2020)
"Agent Raibert Kaminski and the crew of the Transtemporal Vehicle Kleio have made a shocking discovery out in the unknown reaches of the multiverse. They've stumbled across a temporal implosion that has claimed two whole universes, and neither Raibert nor his crew can figure out what caused this calamity other than it had something to do with reckless time travel. The Kleio speeds back to [its] home universe of SysGov with this dire report, but an audacious plan is put into effect before they arrive: old colleagues of Raibert's from the Antiquities Rescue Trust, together with a version of Samuel Pepys transplanted from the 17th century into the 30th, have proposed an expedition into the past"--
Keywords: Pepys, Samuel, -- 1633-1703 -- Fiction; Time travel -- Fiction; Science fiction; Time-travel fiction